Japanese preschoolers' evaluation of circular and non-circular arguments. Issue 5 (3rd September 2018) - Mercier, Hugo; Sudo, Mioko; Castelain, Thomas; Bernard, Stéphane; Matsui, Tomoko
Abstract: Observational and experimental data have revealed that preschoolers possess some argumentation skills, both in the production and the evaluation of arguments. However, these skills might have been fostered by the particular cultural context of Western middle- and upper-classes families, to which most children studied belong. Some data suggests that children in other cultures possess at least some of these skills, but no experimental data had been gathered in Eastern cultures. These cultures are supposed to frown on argumentation, and might thus be less conducive to the early development of argumentation skills. We test the emergence of argument evaluation skills in Japanese 5-year-olds by presenting them with a choice between endorsing a strong, perceptual argument, and a weak, circular argument. A first experiment revealed a trend in the direction of the strong argument. A second experiment that addresses some methodological concerns of the first demonstrates a significant tendency to follow the strong argument. These results are similar to those previously gathered in two other cultures (Swiss and Maya), and suggest that some basic argumentation skills are early developing across cultures.